2019
DOI: 10.1002/slct.201802033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystal Phase of MnO2 with Similar Nanorod‐Shaped Morphology on the Catalytic Performance of Benzene Combustion

Abstract: Four manganese oxides with different crystal structures in the similar nanorod‐shaped morphology were synthesized and investigated for the catalytic combustion of benzene. The physicochemical properties of the materials were characterized by N2 physisorption‐desorption, transmission electron microscope (TEM), X‐ray photoelectron spectroscopy (XPS), Raman spectra, O2 temperature programmed desorption (O2‐TPD) and temperature programmed surface reaction (TPSR). The catalytic activities on benzene combustion over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…Hu et al 146 found that the order of catalytic activities on benzene combustion over MnO 2 with different phase structures was γ-MnO 2 > β-MnO 2 > α-MnO 2 > δ-MnO 2 . The surface adsorbed oxygen species concentration and low temperature O 2 desorption of these manganese oxides were in good agreement with the sequence of their catalytic performance on benzene combustion.…”
Section: Application In Catalytic Oxidationmentioning
confidence: 99%
“…Hu et al 146 found that the order of catalytic activities on benzene combustion over MnO 2 with different phase structures was γ-MnO 2 > β-MnO 2 > α-MnO 2 > δ-MnO 2 . The surface adsorbed oxygen species concentration and low temperature O 2 desorption of these manganese oxides were in good agreement with the sequence of their catalytic performance on benzene combustion.…”
Section: Application In Catalytic Oxidationmentioning
confidence: 99%
“…Heterogeneous catalysis generally involves the cleavage and formation of chemical bonds for the reactant and the product on the surface of a catalyst, and these elementary steps could be rationally expected to be closely associated with the coordination environment or active sites of the catalyst surface. Catalyst morphology is a significant tool to investigate these impacts on heterogeneous catalysis because a morphology-controllable catalyst could expose specific crystal planes, which had different coordination environments. ,, Therefore, morphology effects have been paid much attention for investigating heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analysis of the activity of MnO 2 with different crystal forms, Hu et al. conclude that the activity sequence of these MnO 2 phases is γ ‐MnO 2 > α ‐MnO 2 > δ ‐MnO 2 . The existence of γ ‐MnO 2 could be more favorable to desulfurization.…”
Section: Resultsmentioning
confidence: 99%